ANALISIS KUALITAS AIRTANAH BEBAS DI KECAMATAN TANGGULANGIN SEBAGAI DAMPAK SEMBURAN LUMPUR LAPINDO SIDOARJO - , REZA FAUZIAH WAHYUNI; , Prof. Dr. Sudarmadji, M.Eng, Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted in the District Tanggulangin, Sidoarjo, to determine the unconfined groundwater pollution due to the Lapindo mudflow which appeared in 2006. The environmental indicator including BOD, COD, phenol and H2S were used to assess the pollution severity. This study aimed to determine the condition of unconfined groundwater at Tanggulangin District in terms of physical (conductivity, color, taste, smell) and chemical properties (pH, BOD, COD, Phenol, and H2S) and to assess the properness of unconfined groundwater quality at Tanggulangin District to be used as a source of drinking water. Stratified Sampling method based on water conductivity level which was measured after the groundwater depth was defined and Systematic grid Method to determine the location of wells used for mapping the direction of groundwater flow were used. Furthermore, data obtained including laboratory test result were subjected to descriptive, graphical and spatial analysis. The result showed that the groundwater around the studied area have largely been polluted, indicated by the high values of BOD, COD, phenols and H2S, which have exceeded the limit set for Water Quality Standards, issued through Indonesia Government Regulation No. 82/2001. Samples which were collected from the closer location to Lapindo mud ponds tended to have higher COD value compared to the further area. BOD values and phenol level were higher in samples collected from the further area to the ponds, especially in dense residential areas. However, the levels of H2S in Kedensari Village groundwater whose location is very close to the mud ponds was found to be higher than the other samples. In addition, the groundwater also smelled which indicated the contamination by the water of Lapindo mud ponds. The villages around the Lapindo ponds have lower elevation than the ponds, thus the pollutants flowed to the areas with lower groundwater surface. The BOD, COD, phenols and H2S levels in some of the samples which exceeded the limit of drinking water quality standard indicated that the groundwater in those areas cannot be used as drinking water.